2002
DOI: 10.1111/j.1540-8183.2002.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal Occluder and Rheolytic Thrombectomy of a Saphenous Vein Graft Lesion with a Large Associated Thrombus

Abstract: Percutaneous intervention in thrombus-containing lesions is frequently associated with complications, including distal embolization and no-reflow. In saphenous vein bypass grafts (SVG), friable atheroma and associated thrombus make interventions particularly difficult. Distal protection strategies are in development, but complete protection with removal of all potentially embolic material is challenging. This case illustrates a novel technique using a distal occluder balloon and rheolytic thrombectomy followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Percutaneous intervention of saphenous vein grafts is challenging and is associated with high risk of distal embolization, slow flow, and no‐reflow [1, 2]. Various protective devices, including balloon occluders and filters, are designed to handle distal embolization and minimize the likelihood of large burdens of atherothrombotic materials migrating downstream [3, 4]. In randomized clinical trials, both the balloon and the filter techniques showed similar efficacy in reducing distal embolization, target lesion and vessel revascularization, myocardial infarction and death [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous intervention of saphenous vein grafts is challenging and is associated with high risk of distal embolization, slow flow, and no‐reflow [1, 2]. Various protective devices, including balloon occluders and filters, are designed to handle distal embolization and minimize the likelihood of large burdens of atherothrombotic materials migrating downstream [3, 4]. In randomized clinical trials, both the balloon and the filter techniques showed similar efficacy in reducing distal embolization, target lesion and vessel revascularization, myocardial infarction and death [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Various protective devices, including balloon occluders and filters, are designed to handle distal embolization and minimize the likelihood of large burdens of atherothrombotic materials migrating downstream [3,4]. In randomized clinical trials, both the balloon and the filter techniques showed similar efficacy in reducing distal embolization, target lesion and vessel revascularization, myocardial infarction and death [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, in the days before embolic devices were approved in the United States, we advocated a guiding catheter aspiration technique [7] that is still useful in cases in which an embolic protection device is not appropriate. Others have reported success with techniques that include a distal occluder balloon and rheolytic thrombectomy followed by stent deployment in the SVG [8].…”
mentioning
confidence: 99%